Unholy war terror in the name of Islam - Esposito, John L. (Oxford University Press, 2002)
The devastating September 11 attacks left the world stunned, angry, and uncomprehending. When it became clear that they had been committed in the name of Islam, people struggled to learn more about the religion used to justify these acts. The author clearly and carefully explains the teachings of Islam--the Quran, the use of violence, and terrorism. He also chronicles the rise of extremist groups and examines their worldview and tactics.